The impact of the COVID-19 pandemic on the professional commitment of male nursing students in China: a descriptive comparative study - Huijie Wang; Shuyuan Cheng; Peixuan Liu; Zhifen Feng; Guozeng Zhang (BMC, 2024)
Abstract Background The social culture, gender stereotypes, and social status of nursing in China impact the professional commitment of male nursing students. Increasing the professional commitment of male nursing students is critical for alleviating the shortage of nurses and addressing the gender gap. The outbreak of the COVID-19 pandemic has caused widespread public concern about the nursing profession and may have changed people's perception of the profession, which in turn may have a positive impact on the professional commitment of male nursing students in China. Objective This research aimed to assess how the COVID-19 pandemic affected the professional commitment of male nursing students in China and to analyze the impact of the COVID-19 pandemic on potential factors that might affect their professional commitment. Methods A descriptive comparative study was conducted. This study involved total 368 male nursing students from five 4-year universities in Henan Province, China. 190 male nursing students were included before the COVID-19 pandemic (October to November 2019) and 178 were included after the COVID-19 pandemic (April to May 2023). The data, such as the sociodemographic characteristics and professional commitment of the two samples, were collected using a paper-and-pencil questionnaire. The research instruments used included the Professional Commitment Scale, the Multidimensional Scale of Perceived Social Support and the General Self-efficacy Scale. The data analysis employed χ2-tests, t-tests and hierarchical regression models. Results The proportion of Chinese male nursing students who are interested in nursing and do not intend to leave the major has increased after the pandemic (65.17% vs. 29.47%, 61.80% vs. 39.47%, respectively). Male nursing students exhibited greater professional commitment (3.30 ± 0.63) after the pandemic compared to before the pandemic (2.77 ± 0.43). The various factors, such as grade, intend to leave the major, interest in nursing, social support, and general self-efficacy, were linked to professional commitment of male nursing students in China. Conclusions Male nursing students in China exhibited greater professional commitment after the pandemic. This phenomenon may be attributed to the public's increased recognition of the significance of nursing work during the pandemic, and the social status and image of nursing profession have been improved. Given the changes brought about by the COVID-19, strategies should be considered by nursing decision makers and schools to strengthen the professional commitment of male nursing students and increase the number of male nurses in the post-pandemic era.